The Relationship of Knowledge, Attitudes, and Family History of Breast Cancer to Breasr Self Examination (BSE) Behavior on Women - Meilina, Ayu Yeli; Masluroh, Masluroh (GLOBAL HEALTH SCIENCE GROUP, 2024)
Breast cancer is the most common cancer experienced by women with an estimated 1.67 million new cancer cases diagnosed. The World Cancer Organization and the World Health Organization estimate an increase in cancer incidence by 2030, and the majority occur in developing countries including Indonesia. Breast self-examination (BSE) is an easy way to detect lumps as early cancer. But there are still many women who don't do it. The aimed of this study was to conduct an analysis of the effect of knowledge about the benefits of BSE, attitudes, and history of cancer in families with BSE examination. Cross-sectional design study. The study was conducted at the Pabuaran Health Center (Puskesmas) from December 2023 to January 2024. The sample used in this study was 43 women of childbearing age. The independent variables in this study were: knowledge, attitude, and history of breast cancer. The dependent variable is the behavior of the BSE examination. The research instrument is a questionnaire. The bivariate analysis used in this study was a multiple logistic regression test. Multivariate results showed a relationship between knowledge and attitudes towards BSE behavior (knowledge p value 0.019 < 0.05. attitude p value 0.031 < 0.05), but there was no relationship between family breast cancer history and BSE behavior p value 0.560 < 0.05.